The Influence of Work Motivation and Training on the Competence of Pharmaceutical Workers in Makassar City - Irfan Kurniawan; Siti Haerani; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
Motivation is a desire in a person that causes the act of that person. Meanwhile, training is an effort to improve the performance of the employee in their current job or in other jobs that they will hold. The aim of this study is to find out how much motivation and training affect the competence of pharmacists in Makassar City. There is 150 personnel of pharmacy (pharmacist) as the respondents of this study, which are 43 men and 107 women. Data collection techniques using a questionnaire with a descriptive quantitative method. Questions in the questionnaire are in the form of questions that uses scale of Likert 1-5. The analysis step of the research is preceded by an instrument of research, which is collecting data and processing the data obtained in the questionnaire by giving the score of each statement based on a scale of Likert, and conduct test validity, test reliability, test for normality and test regression. The test regression was multiple regression. The data processing is conducted by using SPSS 22. The results of the study indicate (1) the motivation is positively and significantly affected to competence; (2) training has a positive and significant effect on competence; (3) motivation and training have a positive and significant effect on competence.